HOME IN THE POETRY OF SAUDI ARABIA POETS: Taher Zamakhshari an Example of a Distinguished Arab - Dahami, Yahya Saleh Hasan (UIN Sumatera Utara, 2025)
Poets always glorify and praise the homeland. The homeland is an absolutely crucial matter among Saudi poets, Arab poets, and, I can say, among every thoughtful human being. Several Saudi poets dealt with the same issue, presenting us with gorgeous lyrical poetic pieces praising their homeland, the Kingdom of Saudi Arabia. Through the poem